A second independent audit of electroconvulsive therapy in England, 2019: Usage, demographics, consent, and adherence to guidelines and legislation. (16th March 2021) - Read, John; Harrop, Christopher; Geekie, Jim; Renton, Julia; Cunliffe, Sue
Abstract : Objectives: To assess progress towards improving the administering of electroconvulsive therapy (ECT) in England since an audit covering 2011, 2013, and 2015. The same information was gathered, for 2019, on usage, demographics, consent, and adherence to national guidelines and the Mental Health Act. Design and Methods: Freedom of Information Act requests were sent to 56 National Health Service Trusts. Results: Thirty‐seven trusts (66%) provided data. The gradual decline in the use of ECT in England has levelled off at about 2, 500 people per year. There was a 47‐fold difference between the Trusts with the highest and lowest rates per capita. Most recipients are still women (67%) and over 60 (58%). Only one Trust could report how many people received psychological therapy prior to ECT, as required by government (NICE) guidelines. More than a third of ECT (37%) is still given without consent, with 18% of Trusts non‐compliant with legislation concerning second opinions. There were slight declines, compared to a previous audit, in the use of standardized depression scales, down to 30%, and standardized measures of cognitive dysfunction, down to 24%. Only six Trusts provided any data for positive outcomes and seven for adverse effects. None provided data on efficacy or adverse effects beyond the end of treatment. Twelve Trusts used identical sentences to each other, verbatim, in response to one or more questions. Conclusions: Given the apparent failure of current monitoring and accrediting of ECT clinics in England, by the Royal College of Psychiatrists' ECT Accreditation Service (ECTAS), an independent government sponsored review is urgently needed. Practitioner points: Psychologists and other mental health staff should ensure that people are offered evidence‐based psychological treatments before being offered E.C.T. All staff should ensure that patients are fully informed of the high risk of memory loss and the smaller risk of cardiovascular failure and mortality. Individuals receiving ECT should be closely monitored for adverse cognitive effects, and treatment immediately terminated if these become apparent. Because of increased risk of memory loss for women and older people, the use of ECT should be kept to a minimum and avoided where possible, with these two groups.